Wählen zwischen Recht und Pflicht: Ergebnisse einer Exkursion der Ostasienwissenschaften in die Provinz Sichuan, VR China - Anja-Désirée Senz (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2004)
In August 2001, students of East Asian Studies travelled for field research to Sichuan province in Southwest China. The excursion was organized and supervised by Prof. Dr. Thomas Heberer and Anja-Désirée Senz. In the rural districts of South Sichuan the group conducted qualitative and quantitative empirical research on village elections. These elections were introduced in China nationwide in 1998 and are international highly recognized, because of there potentially impact on political reforms in China. The objective of the research was to analyse the influence of village elections on the political consciousness of the rural population. Some of the results are being presented in the following article.
Keywords: 330